Mediation-Moderation Modeling for Marketing in Supply Chain Management - Robert Kristaung; Sri Vandayuli Riorini (International Journal of Supply Chain Management, 2020)
Abstract- This paper aimed to explore and remap the functions and roles of mediating and moderating variables from various research papers and their use in supply chain management marketing research. The interface areas investigated between marketing and logistics/supply chain management in marketing research. The literature review method used refers to using the thematic content analysis approach and qualitative analysis. The research findings were a single mediation model with full mediation classification, partial mediation, complementary mediation, and competitive mediation. Both single moderation models with classification homologizer moderation, quasi moderation, and pure moderation. Finally, a combination of mediation and moderation models with separated mediation-moderation classification and complementary mediation-moderation. With the increasingly complex modeling that is proposed and tested, the clarity of the statistical tools used is very important to disclose as one component of the assessment of qualitative supply chain management marketing research.